2020
DOI: 10.2459/jcm.0000000000001116
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic clustering of heart failure with preserved ejection fraction reveals different rates of hospitalization

Abstract: Aims Approximately 50% of patients with heart failure have preserved (≥50%) ejection fraction (HFpEF). Improved understanding of the phenotypic heterogeneity of HFpEF might facilitate development of targeted therapies and interventions. Methods This retrospective study characterized a cohort of patients with HFpEF based on similar clinical profiles and evaluated 1-year heart failure related hospitalization. Enrolment, medical and pharmacy data were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…Of the ten studies three suggested that there were six phenotypes and six studies suggest that there were only three phenotype (Table 2 (Tab. 2) ; References in Table 2: Casebeer et al, 2021[ 12 ]; Cohen et al, 2020[ 18 ]; Gu et al, 2021[ 37 ]; Hedman et al, 2020[ 43 ]; Kao et al, 2015[ 52 ]; Nouraei and Rabkin, 2021[ 79 ]; Schrub et al, 2020[ 107 ]; Segar et al, 2020[ 109 ]; Shah et al, 2015[ 112 ]; Woolley et al, 2021[ 131 ]). One study reported that the 'optimal number of clusters was six', but due to the small size of two clusters ( n = 3 and n = 2), they focused on the (remaining four) patient clusters (Woolley et al, 2021[ 131 ]).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the ten studies three suggested that there were six phenotypes and six studies suggest that there were only three phenotype (Table 2 (Tab. 2) ; References in Table 2: Casebeer et al, 2021[ 12 ]; Cohen et al, 2020[ 18 ]; Gu et al, 2021[ 37 ]; Hedman et al, 2020[ 43 ]; Kao et al, 2015[ 52 ]; Nouraei and Rabkin, 2021[ 79 ]; Schrub et al, 2020[ 107 ]; Segar et al, 2020[ 109 ]; Shah et al, 2015[ 112 ]; Woolley et al, 2021[ 131 ]). One study reported that the 'optimal number of clusters was six', but due to the small size of two clusters ( n = 3 and n = 2), they focused on the (remaining four) patient clusters (Woolley et al, 2021[ 131 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Phenogroup 1 patients had the lowest prevalence of heart failure comorbidities and highest mean age; Phenogroup 2 patients had higher prevalence of metabolic syndrome and pulmonary disease, despite younger mean age. Phenogroup 3 patients had higher prevalence of cardiac arrhythmia and renal disease (Casebeer et al, 2021[ 12 ]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations